Fenomena Transformasi Koperasi Konvensional Menjadi Koperasi Syariah di Kota Tangerang - Wahyu Hidayat, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The transformation of conventional cooperatives into sharia cooperatives is an interesting phenomenon to study. The motivation for transformation into a sharia cooperative occurred due to several factors, both internal and external. This research uses a qualitative phenomological method approach. By collecting data through participant observation to be able to find out the essential phenomena of the participants. Based on the results of data analysis and interviews conducted by researchers regarding the phenomenon of cooperatives transforming into Sharia Cooperatives (KSPPS) or opening Sharia Business Units (USPPS) in Tangerang City, it can be concluded that religious awareness or religiosity, perceptions about sharia cooperatives, training about sharia economics , sharia cooperative products and sharia cooperative business opportunities have encouraged the phenomenon of transformation into sharia cooperatives and sharia business units in cooperatives in Tangerang City. This further strengthens the positive image of Tangerang City as a city with good morals, which imbues the values of the social order.